2002
DOI: 10.1161/01.cir.0000038891.06306.ba
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Postexercise Cardiovascular Recovery and Its Determinants in Patients After Right Ventricular Outflow Tract Reconstruction

Abstract: Background-Abnormal responses of heart rate (HR) and oxygen uptake (V O 2 ) during exercise characterize patients after right ventricular outflow tract reconstruction (RVOTR) for congenital heart defects. However, little is known about the postexercise dynamics. Methods and Results-We evaluated postexercise cardiovascular dynamics in 52 patients after closure of an atrioventricular septal defect (group A), 79 patients after RVOTR (group B), and 44 control subjects. HR variability, arterial baroreflex sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…The blunted heart rate response during exercise in patients with repaired TOF is well documented [12,24]. Hemodynamic changes induced by pregnancy such as increased HR, cardiac output, volume overload and decreased systemic vascular resistance [24] were similarly observed during exercise due to oxygen demand of the body and fetus.…”
Section: Impaired Hr Response During Pregnancy In Patients With Repaimentioning
confidence: 99%
See 1 more Smart Citation
“…The blunted heart rate response during exercise in patients with repaired TOF is well documented [12,24]. Hemodynamic changes induced by pregnancy such as increased HR, cardiac output, volume overload and decreased systemic vascular resistance [24] were similarly observed during exercise due to oxygen demand of the body and fetus.…”
Section: Impaired Hr Response During Pregnancy In Patients With Repaimentioning
confidence: 99%
“…The blunted heart rate response during exercise in patients with repaired TOF is well documented [12,24]. Hemodynamic changes induced by pregnancy such as increased HR, cardiac output, volume overload and decreased systemic vascular resistance [24] were similarly observed during exercise due to oxygen demand of the body and fetus. Ohuchi H, et al reported [12] that parasympathetic nerve activity due to surgical damage are crucial to the HR response during exercise and are the major determinant of individual exercise capacity in patients with right ventricular outflow tract repair.…”
Section: Impaired Hr Response During Pregnancy In Patients With Repaimentioning
confidence: 99%
“…We performed cardiac catheterization with cineventriculography in 47/51 Fontan and all RVOTR patients to evaluate post-operative hemodynamics, while 25 controls underwent follow-up selective coronary angiography as described before [7][8][9][10]. We measured pressures in the cardiac chambers and great vessels.…”
Section: Hemodynamicsmentioning
confidence: 99%
“…We measured arterial baroreflex sensitivity (BRS) as an indication of cardiac vagal nervous activity using methodology reported previously [7][8][9]. The ECG, arterial blood pressure (by Finapres, Ohmeda) and respiration were recorded continuously after bolus phenylephrine administration until the blood pressure peaked.…”
Section: Measurement Of Arterial Baroreflex Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation